PENGEMBANGAN ALAT PERMAINAN EDUKATIF ULAR TANGGA DALAM PEMBELAJARAN MATEMATIKA KELAS II SDN 9 NEGERIKATON - Yulita Dwi Lestari; Anisa Urrohmah; Joko Sutrisno AB (STKIP Subang, 2023)
ABSTRACT This research uses development research. This research is motivated by the unavailability of snakes and ladders educational game tools as learning media in mathematics. Snakes and ladders educational game tool media is good to use because it can make it easier for educators to carry out learning, students can also learn while playing so that the process of learning activities feels fun and not boring. Based on the research results, it was obtained that the material validation was 90.38% with the criteria of